Kajian Azaz Manfaat Jembatan Penyeberangan Orang (JPO) di Jalan Sultan Thaha Kota Jambi - Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (Jurnal Civronlit Unbari, 2018)
Pedestrian facilities are often overlooked. Whereas pedestrians include elements of traffic flow that need attention, especially in dense urban areas will be vehicles. The purpose of this research is to know the benefits of the Pedestrian Overpass (JPO) in Jalan Sultan Thaha near WTC Mall of Jambi City. The research conducted is to survey JPO users during peak hours and busy days and compare to the traffic in the research area. The results of the study assessed the suitability of the ferry facilities to the existing requirements and to recommend appropriate facilities can be calculated from the highest crossing volume (P) and vehicle volume (V) at peak hours ie P = 325 pedestrians /hour, V = 2610.75 vehicles./hour. Based on the recommendation of choosing a road crossing facility, it can be concluded that the recommended facilities are Zebra Cross (ZC) crossing facilities and it is not feasible to use JPO. From the percentage data of population growth in the estimation of the number of people who will use pedestrian overpass, it will work at 8 years 3 months ahead. Keyword :  Pedestrian Overpass, Crossers, traffic density